Diet Intervention and Cerebrospinal Fluid Biomarkers in Amnestic Mild Cognitive Impairment - Bayer-Carter, Jennifer L. (2011)
OBJECTIVE: To compare the effects of a 4-week high–saturated fat/high–glycemic index (HIGH) diet with a low–saturated fat/low–glycemic index (LOW) diet on insulin and lipid metabolism, cerebrospinal fluid (CSF) markers of Alzheimer disease, and cognition for healthy adults and adults with amnestic mild cognitive impairment (aMCI). DESIGN: Randomized controlled trial. SETTING: Veterans Affairs Medical Center clinical research unit. PARTICIPANTS: Forty-nine older adults (20 healthy adults with a mean [SD] age of 69.3 [7.4] years and 29 adults with aMCI with a mean [SD] age of 67.6 [6.8] years). INTERVENTION: Participants received the HIGH diet (fat, 45% [saturated fat, >25%]; carbohydrates, 35%–40% [glycemic index, >70]; and protein, 15%–20%) or the LOW diet (fat, 25%; [saturated fat, <7%]; carbohydrates, 55%–60% [glycemic index, <5]; and protein, 15%–20%) for 4 weeks. Cognitive tests, an oral glucose tolerance test, and lumbar puncture were conducted at baseline and during the fourth week of the diet. MAIN OUTCOME MEASURES: The CSF concentrations of β-amyloid (Aβ42 and Aβ40), tau protein, insulin, F2-isoprostanes, and apolipoprotein E, plasma lipids and insulin, and measures of cognition. RESULTS: For the aMCI group, the LOW diet increased CSF Aβ42 concentrations, contrary to the pathologic pattern of lowered CSF Aβ42 typically observed in Alzheimer disease. The LOW diet had the opposite effect for healthy adults, ie, decreasing CSF Aβ42, whereas the HIGH diet increased CSF Aβ42. The CSF apolipoprotein E concentration was increased by the LOW diet and decreased by the HIGH diet for both groups. For the aMCI group, the CSF insulin concentration increased with the LOW diet, but the HIGH diet lowered the CSF insulin concentration for healthy adults. The HIGH diet increased and the LOW diet decreased plasma lipids, insulin, and CSF F2-isoprostane concentrations. Delayed visual memory improved for both groups after completion of 4 weeks of the LOW diet. CONCLUSION: Our results suggest that diet may be a powerful environmental factor that modulates Alzheimer disease risk through its effects on central nervous system concentrations of Aβ42, lipoproteins, oxidative stress, and insulin.